ANALISIS FITOKIMIA DAN UJI TOKSISITAS AIR SADAPAN BATANG PISANG MERAH (Musa acuminata Colla ‘Red Dacca’) - Nurul Ade Safitri; Wa Ode Mulyana; Abraham Rahman (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
The ethnobotanical utilization of tap water from the pseudo stem of red banana (Musa acuminata Colla ‘Red Dacca’) to accelerate wound healing and treat infections whose scientific safety profile has not been explored is the background of this research. This operational problem triggers the lack of validation of clinical efficacy standards and the absence of draft information regarding the toxicity threshold of this natural material. The main focus of this scientific study is to analyze the qualitative secondary metabolite content and test its specific toxicity level. The steps of this laboratory research are operated through phytochemical screening and testing the cytotoxic effect of the Brine Shrimp Lethality Test (BSLT) method on Artemia salina Leach larvae samples. The procedure for determining lethal potential is executed in a structured manner by measuring the % mortality of larvae which is then calculated via linear probit statistical analysis. Quantitative data empirically reveals the presence of secondary metabolites in the form of flavonoids, saponins, tannins, triterpenoids, and coumarins. The results of the toxicity test recorded an LC50 parameter value of 9,852.74 μg/mL. The main conclusion confirms that the liquid extract of red banana stem is classified as very safe (non-toxic) because the LC50 value is above the threshold of 1,000 μ"g/mL", but has less potential to be developed as an active anticancer agent. ABSTRAK Pemanfaatan secara etnobotani air sadapan batang semu pisang merah (Musa acuminata Colla ‘Red Dacca’) untuk percepatan penyembuhan luka serta pengobatan infeksi yang belum tereksplorasi profil keamanan ilmiahnya melatarbelakangi penelitian ini. Masalah operasional ini memicu kurangnya validasi standar efikasi klinis serta ketiadaan draf informasi mengenai ambang batas toksisitas bahan alam tersebut. Fokus utama kajian ilmiah ini adalah menganalisis kandungan metabolit sekunder kualitatif serta menguji tingkat toksisitas spesifiknya. Langkah-langkah penelitian laboratorium ini dioperasikan melalui skrining fitokimia serta pengujian efek sitotoksik metode Brine Shrimp Lethality Test (BSLT) terhadap sampel larva Artemia salina Leach. Prosedur penentuan potensi lethal dieksekusi secara terstruktur mengukur %mortalitas larva yang kemudian dikalkulasi via analisis statistik probit linier. Data kuantitatif secara empiris menyingkap keberadaan kandungan metabolit sekunder berupa flavonoid, saponin, tanin, triterpenoid, dan kumarin. Hasil pengujian toksisitas mencatatkan nilai parameter LC50 sebesar 9.852,74 . Simpulan utama menegaskan bahwa ekstrak cairan batang pisang merah tergolong sangat aman (non-toxic) karena nilai LC50 berada di atas threshold 1.000 , namun kurang berpotensi untuk dikembangkan sebagai agen bahan aktif antikanker.